The Effectiveness of Free Halal Certification Services Through the Scheme Self Declare for SMEs in Lampung Province - Astrid Aprica Isabella; Pipit Novila Sari (International Journal of Economics (IJEC), 2023)
Based on the demands of the law that all products circulating in Indonesia must be halal certified, including products produced by MSEs. Food products, beverages, medicines, slaughter services and slaughter must be halal certified. Products that are not yet halal-certified in October 2024 will be subject to sanctions, sanctions ranging from written warnings, administrative fines, to the withdrawal of goods from circulation in accordance with the provisions in PP No. 39 of 2021 (Republic of Indonesia's Ministry of Religion). Therefore, BPJPH as the Halal Product Assurance Organizing Agency is mandated by law to provide convenience for MSE actors, namely by facilitating free halal certification (Sehati) through a self-declared mechanism. The purposes of this research are (1) to find out how far self-declaring halal certification services have been absorbed by UMK actors, especially in Lampung Province, (2) to analyze BPJPH performance regarding self-declaring in accordance with the target given, namely in October 2024 UMK products are already certified legal. In this study used qualitative methods. The approach used in this study is an approach through a normative approach through sample testing and MSME data as the main data which is then processed qualitatively based on existing data. The research samples that became the object of this study were the UMK of Bandar Lampung City, UMK of South Lampung Regency, and UMK of Mesuji Regency. The number of respondents who were sampled in the study were 30 respondents from 10 UMK in Bandar Lampung City, 10 UMK in South Lampung Regency, and 10 UMK in Mesuji Regency. The results of the study show that in the past year self-declared halal certification has been well socialized, but UMK hopes that the free halal certification quota will be extended/added so that it is absorbed evenly both in cities and in remote districts.